Oculocutaneous albinism and bleeding diathesis due to a novel deletion in the HPS3 gene - Marek-Yagel, Dina; Abudi-Sinreich, Shachar; Macarov, Michal; Veber, Alvit; Shalva, Nechama; Philosoph, Amit Mary; Pode-Shakked, Ben; Malicdan, May Christine V.; Anikster, Yair (Frontiers in Genetics, 2022)
Hermansky-Pudlak syndrome (HPS) is a group of rare autosomal recessive disorders characterized by oculocutaneous albinism (OCA) and bleeding diathesis. To date, 11 HPS types have been reported (HPS-1 to HPS-11), each defined by disease-causing variants in a specific gene. Variants in the HPS1 gene were found in about 15% of HPS patients, most of whom harbor the Puerto Rican founder mutation. Here, we report six affected individuals from three non-consanguineous families of Ashkenazi-Jewish descent, who presented with OCA and multiple ecchymoses, with normal platelet number and size. Linkage analysis indicated complete segregation to HPS3. Sequencing of the whole coding region and the intron boundaries of HPS3 revealed a heterozygous c.1163+1G>A variant in all six patients. Long range PCR amplification revealed that all affected individuals also carry a 14,761bp deletion that includes the 5’UTR and exon 1 of HPS3, encompassing regions with Long Interspersed Nuclear Elements (LINEs). The frequency of the c.1163+1G>A splice site variant was found to be 1:200 in the Ashkenazi-Jewish population, while the large deletion was not detected in 300 Ashkenazi-Jewish controls. These results present a novel HPS3 deletion mutation and suggest that the prevalence of HPS-3 in Ashkenazi-Jews is more common than previously thought.